Structural Analysis of Anti-Hapten Antibodies to Identify Long-Range Structural Movements Induced by Hapten Binding - Al Qaraghuli, Mohammed M.; Kubiak-Ossowska, Karina; Ferro, Valerie A.; Mulheran, Paul A. (Frontiers in Molecular Biosciences, 2021)
Antibodies are well known for their high specificity that has enabled them to be of significant use in both therapeutic and diagnostic applications. Antibodies can recognize different antigens, including proteins, carbohydrates, peptides, nucleic acids, lipids, and small molecular weight haptens that are abundantly available as hormones, pharmaceuticals, and pesticides. Here we focus on a structural analysis of hapten-antibody couples and identify potential structural movements originating from the hapten binding by comparison with unbound antibody, utilizing 40 crystal structures from the Protein Data Bank. Our analysis reveals three binding surface trends; S1 where a pocket forms to accommodate the hapten, S2 where a pocket is removed when the hapten binds, and S3 where no pockets changes are found. S1 and S2 are expected for induced-fit binding, whereas S3 indicates that a pre-existing population of optimal binding antibody conformation exists. The structural analysis reveals four classifications of structural reorganization, some of which correlate to S2 but not to the other binding surface changes. These observations demonstrate the complexity of the antibody-antigen interaction, where structural changes can be restricted to the binding sites, or extend through the constant domains to propagate structural changes. This highlights the importance of structural analysis to ensure successful and compatible transformation of small antibody fragments at the early discovery stage into full antibodies during the subsequent development stages, where long-range structural changes are required for an Fc effector response.